ETHICS OF SCIENCE: MORAL PRINCIPLES AND THEIR ROLE IN THE DEVELOPMENT OF SOCIETY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article examines the importance of science ethics as a system of values regulating scientific activity and the personal responsibility of the researcher to society. The main attention is paid to how morality and spirituality contribute to the development of personality, as well as the influence of ethical norms on maintaining harmony between science, nature and society. The key ideas of science ethics proposed by R. Merton, including universalism, communism, selflessness and organized scepticism, as well as the contribution of other scientists, such as N. Wiener and M. Polanyi, to the development of ethical norms are analysed. A historical overview of the role of ethics in limiting and supporting freedom of research from antiquity to the present day is given. Moral aspects in scientific activity and their necessity in maintaining a balance between scientific progress and the moral responsibility of scientists to humanity are considered.